THE IMPACT OF THE DEVELOPMENT OF THE SPORTS SECTOR ON THE ECONOMY OF UZBEKISTAN - Soy , Marina; Sunnatov , Qudratilla (Scientific practical conference, 2025)
The following aspects are widely publicized in this work: The purpose and tasks, directions, history of development of the system of physical culture of the Republic of Uzbekistan in the society, as well as the features of development of the system of physical culture in the Republic of Uzbekistan in the former Soviet Union and the years of independence, reforms and their positive effects are widely publicized.